Cell Block Preparation as an Important Tool in Addition to the Conventional Cytological Smears - Devanshi Gosai (Medical Research and Its Applications Vol. 1, 2024)
Background: For the detection of malignancy in the serous fluids of the body, cytological examination of the fluid is very important. It is also of prime importance and seems difficult to differentiate malignant cells from reactive mesothelial cells during fluid cytology. The cell block preparation is a useful and additive diagnostic tool when cellular features in cytology are inconclusive or suspicious. The aim of the study was to assess the utilization of the cell technique as an additional tool along with the conventional smears that we are using in routine practice. Methods: The present study included 200 cases of effusion fluids, out of which 117 were pleural, 82 were peritoneal and 1 was pericardial from a tertiary care hospital, Vadodara, India. The patient presented with complaints of ascites, pleural effusions or pericardial effusions were included in the study. A total of 200 body (effusion) fluids were examined by the conventional cytological smears as well as by the cell block technique. Results: Out of 200 cases, there were 110 (55%) males and 90 (45%) were females. The cases of pleural effusion were more common amongst the males i.e. 77 (38.5%) whereas only 40(20%) cases were noted among the female. In our study of 200 cases, the maximum number of cases were inflammatory 177 (88.5%) while malignancy was detected in 27 (11.5%) cases. Pleural effusion cases were the commonest among all the cases followed by peritoneal effusion cases and pericardial effusion cases. Conclusion: The diagnostic of cancer cell yield increases when we use the cell block preparation method along with the conventional smears because the architectural patterns and cell morphology are very well preserved in cell block as compared to the smears.